IBM Storage Fusion product guide - Herd, Jon; Danner, Daniel; Koester, Axel (IBM Redbooks, 2022)
This IBM® Redbooks® publication offers a short overview of IBM's integrated environment for container workloads, IBM Storage Fusion. The product comes in two variants, IBM Storage Fusion HCI System including all required hardware, and IBM Storage Fusion SDS (software-only) for deployment in public or private Clouds. This paper has been updated with the 2.5.1 release only for IBM Storage Fusion and the 2.5.2 release of IBM Storage Fusion HCI System.